Impact of Corona virus pandemic on wastewater characteristics, treatment, and water reuse in a municipal plant - Hamoda, Mohamed F.; AL Rashidi, Noura S. (Frontiers in Environmental Engineering, 2023)
The COVID-19 pandemic is considered one of the most significant threats to health. The effect of the pandemic on performance of wastewater treatment plants has not received much attention in the literature. This study assessed the impact of Coronavirus pandemic on the wastewater quantity, characteristics, treatment processes, and water reuse in Kuwait. It focused on three municipal wastewater treatment plants (WWTPs) with different design capacities, namely Sulaibiya (600,000 m 3 /d), Kabd (180,000 m 3 /d), and Umm Al-Hayman (27,000 m 3 /d), all using tertiary treatment. Daily data records were obtained on influent and effluent over the years 2018 to 2020 (before and during the pandemic). In addition, influent and effluent samples were collected from the Sulaibiya and Kabd plants for laboratory analysis to determine the effect of increase in the use of home disinfectants. The results indicate an increase (<50%) in the average daily flow rates received in WWTPs during the 2020 home quarantine lockdowns. Statistical analysis showed stability of the Sulaibiya in BOD5, COD, and TSS removal efficiency while a decrease in the Kabd and UAH plants removal efficiency was observed during the pandemic. During the lockdown period, GC-MS analysis showed a high probability of chloroxylenol (>90), one of the main components of Dettol disinfectant, existing in the raw wastewater samples while the GC-FID analysis indicated the presence of (PAH) as emerging contaminants, at higher concentrations in the influent and effluent samples. The pandemic adversely affected wastewater treatment plant performance and excessive use of Dettol disinfectant by homes resulted in the presence of objectionable organic pollutants in the tertiary-treated effluent which would impair water reuse. Reverse osmosis process used in Sulaibiya plant proved to be effective in removing residual organics and improving effluent quality for reuse during the pandemic.